1975
DOI: 10.1111/j.1600-0765.1975.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement factors in gingival crevice material from healthy and inflamed gingiva in humans

Abstract: The presence and levels of complement factors C3, C4, C5, and C3 proactivator, were determined by electroimmuno assay in gingival cervice material from five individuals with healthy gingiva and from six patients with chronically inflamed gingiva. Higher concentrations of C3 and C4 were found in samples from chronically inflamed gingiva when compared to those healthy gingiva. The amount of C3 in material from healthy as well as from inflamed gingiva was related to that in plasma, when the albumin in plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 23 publications
9
72
0
Order By: Relevance
“…Moreover, GCF collected from periodontitis patients contains activated complement fragments at higher concentrations than in GCF from healthy individuals [72, 7881]. Consistent with this, complement components and cleavage products are readily detected in chronically inflamed gingiva, whereas complement is undetectable or present at lower levels in healthy gingival biopsy samples [71, 73, 76, 77, 8284].…”
Section: Clinical Evidence Linking Complement To Periodontitismentioning
confidence: 86%
“…Moreover, GCF collected from periodontitis patients contains activated complement fragments at higher concentrations than in GCF from healthy individuals [72, 7881]. Consistent with this, complement components and cleavage products are readily detected in chronically inflamed gingiva, whereas complement is undetectable or present at lower levels in healthy gingival biopsy samples [71, 73, 76, 77, 8284].…”
Section: Clinical Evidence Linking Complement To Periodontitismentioning
confidence: 86%
“…Both immunoglobulin and complement components have been identified in crevicular fluid. [55][56][57] Nisengard and Jarrett 58 reported that subgingival bacteria were coated in vivo with immunoglobulin and complement.…”
Section: Discussionmentioning
confidence: 98%
“…Microorganisms in gingival sulcus are immersed in GCF, which is a serum-derived tissue exudate. Since complement components are present in GCF at up to 70% of serum concentration (30) and in vivo there is high level of complement activation in gingival fluid of patients with periodontitis (31, 32), successful evasion of complement is paramount for the survival of T. forsythia in the periodontal pockets. One such strategy of defense against complement developed by T. forsythia appears to depend on the production of karilysin, which we now show is not only able to degrade complement factors C4 and C5 but also MBL and ficolin-2 and -3, which are crucial molecules enabling recognition of the majority of pathogens without a need of previous exposure and presence of specific antibodies.…”
Section: Discussionmentioning
confidence: 99%